(untitled) (Don Bosco Institute of Technology Delhi Journal of Research, 2025)
In the digital era, online transactions are integral to everyday life—from grocery shopping and clothing purchases to streaming services like Netflix and Amazon Prime. E-Commerce has progressed beyond simple transactions, now leveraging intelligent systems for personalized user experiences via recommendation engines analyzing user behavior, reviews, and past transactions. This transformation is largely powered by the integration of Artificial Intelligence (AI), Machine Learning (ML), and Deep Learning (DL). Over the last decade, this convergence has garnered substantial academic attention. This study presents a bibliometric analysis of 2,464 peer-reviewed publications from 2018 to 2025, sourced from the Dimensions database and filtered through the PRISMA framework and UGC CARE List-II criteria. The analysis explores publication trends, influential authors and institutions, significant countries, high-impact papers, and emerging thematic clusters. The findings reveal an uptrend in research activity, heightened technological integration, and shifting research priorities. The study offers a roadmap for future inquiry at the intersection of E-Commerce and AI technologies.